Influence of sex and maximum strength on reactive strength index-modified - Beckham, G. K.; Suchomel, T. J.; Sole, C. J.; Bailey, C. A.; Grazer, J. L.; Kim, S. B.; Talbot, K. B.; Stone, M. H. (Journal of Sports Science & Medicine, 2019)
Reactive strength index-modified (RSImod) is a measure of lower body explosiveness calculated by dividing jump height by time to takeoff. RSImod is different between stronger and weaker athletes and between males and females. The purpose of this study was to evaluate differences in RSImod between males and females while controlling for maximal strength and lower body explosiveness. Forty-three female and fifty-eight male Division-I athletes performed countermovement jumps on a force plate during unloaded (0kg) and loaded (20kg) conditions. We used an ANCOVA to test whether RSImod is different between sexes conditioning on relative maximum strength (PFa) and average RFD 0-200ms (RFD200) measured during the isometric mid- thigh pull (IMTP). Differences of 0.087 (95% CI: 0.040-0.134; p = 0.0005) and 0.075 (95% CI: 0.040-0.109, p < 0.0001) were observed for RSImod between sexes in unloaded and loaded conditions, respectively. A male with PFa of 186 (grand mean of the sample) and RFD200 of 6602 N/s (grand mean of the sample) is predicted to have 28% greater RSImod than a female of similar PFa and RFD200. Maximum strength development should be a primary aim of training in female athletes, in addition to other trainable factors, such as stiffness and RFD.